Applications and impacts of Internet of Things (IoT) in Logistic industry in Vietnam - Phong, Bui Hai; Bach, Tran Xuan; Khanh, Nguyen Bao; Bach, Pham Dang Viet; Tuan, Nguyen Minh; Minh, Pham Quang; Tue, Vu Gia (International Journal of Scientific Research and Management (IJSRM), 2025)
Vietnam’s logistics ecosystem has rapidly developed. Vietnam logistic industry is listed in top Asian countries in the field. In recent years, high technologies have been applied in Vietnam logistics such as Artificial intelligence (AI), Big data, Cloud computing and Internet of things (IoT). The applications of IoT support the fast development and less risk for logistics. The paper presents the applications and impacts of IoT for Vietnam logistic sector. Moreover, the numerical analysis of IoT applications helps us to emphasize the important role of IoT for Vietnam logistics. The recommendations in future is given for further development of IoT for Vietnam logistics.